Bridging Perception and Practice: How Primary Teachers Adapt Instruction Based on Student Learning Styles - Joice Sitokkonni; Amirullah Amirullah; Fitriyani Fitriyani (Hasanuddin University, 2025)
This qualitative study investigates how primary school teachers adapt their instructional strategies based on their perceptions of students' diverse learning styles in an English as a Foreign Language (EFL) setting. Conducted at IBC School Makassar, Indonesia, the research involved classroom observations and semi-structured interviews with six primary teachers, one principal, and one school supervisor. The findings reveal that while teachers recognize the importance of tailoring instruction to accommodate various learning styles, visual, auditory, reading/writing, and kinesthetic, adaptation in practice is shaped by a combination of personal experience, professional training, and contextual constraints. Teachers consistently employed multimodal strategies, blending visual aids, interactive discussions, and hands-on activities. However, no formal diagnostic tools were used; rather, teachers relied on intuition and continuous classroom observation. Institutional factors such as large class sizes, limited resources, and time constraints often impeded the full implementation of differentiated instruction. Despite these challenges, teachers demonstrated flexibility and creativity, using adaptive strategies that reflected a pragmatic response to classroom realities. This study highlights the dynamic interplay between perception and instructional practice in primary education. It underscores the need for ongoing professional development and institutional support to enhance teachers’ ability to personalize instruction. The findings offer implications for educational policy and teacher training, particularly in implementing student-centered approaches under curriculum reforms like Indonesia's Kurikulum Merdeka.